2010
DOI: 10.1111/j.1574-0862.2009.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal protection of F&V imports in the EU: impacts of the entry price system

Abstract: The measures of border protection applied by the European Union (EU) to imports of fruits and vegetables (FV) are complex and usually not well represented in trade models, not only because of the range of instruments still constraining trade, but also because of product differentiation and seasonality in these products. This article assesses the impact of eliminating entry price (EP) constraints applied to a group of FV products. The proposed model is of a partial equilibrium nature and takes seasonality into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Frontier protection has been progressively dismantled by virtue of the successive Euro‐Mediterranean Trade Agreements (see García Álvarez‐Coque et al . ); in the case of green pepper, custom duties charged to Morocco and other competitors were completely eliminated in 2003. In terms of public support, the First Pillar payments linked to horticulture have never been comparable to the subsidies received by other agricultural products.…”
mentioning
confidence: 99%
“…Frontier protection has been progressively dismantled by virtue of the successive Euro‐Mediterranean Trade Agreements (see García Álvarez‐Coque et al . ); in the case of green pepper, custom duties charged to Morocco and other competitors were completely eliminated in 2003. In terms of public support, the First Pillar payments linked to horticulture have never been comparable to the subsidies received by other agricultural products.…”
mentioning
confidence: 99%
“…The working of the EPS is well known and widely analyzed by several authors (e.g. Swimbank and Ritson, 1995;Cioffi and dell'Aquila, 2004;Emlinger, Jacquet and Lozza, 2008;Goetz and Grethe, 2009;Emingler, Lozza and Jacquet, 2010;Garcia, Gomez and Villanueva, 2010;Goetz and Grethe, 2010), but a consensus on its effectiveness is still lacking. Furthermore, while «entry prices for many products are probably not protective, and could readily be abolished» (Swinbank, 2011), it is also likely they produce (still unclear) distortive effects deserving further investigations (Winchester, 2011;Li and Beghin, forthcoming).…”
Section: The Authors Are Respectively Post-doc Fellow and Professor Amentioning
confidence: 99%
“…Goetz and Grethe (2009) by mean of a multivariate statistic analysis approach showed that the relevance of the EPS is not homogeneous among different products and origins, being wider for more perishable products and for neighbouring partner countries. Garcia Alvarez Coque et al (2010) found that the removal of the EPS or reduction of the Trigger Entry Price would have moderate impact on prices of European domestic products.…”
Section: Relevance and Effectiveness Of The Entry Price System: An Opmentioning
confidence: 99%
“…Por lo tanto, no sería razonable restringir la apertura solo a los sectores industriales (García Álvarez Coque et al, (2012a); García Álvarez Coque y Jordán Galduf (2006).…”
Section: Justificaciónunclassified